Population parameters of the Phillips kangaroo rat (Dipodomys phillipsii) - Montero-Bagatella, Sandra H.; Cervantes, Fernando A.; González-Romero, Alberto (THERYA, 2023)
Populations respond dynamically to biotic and abiotic changes in their habitat. The identification and description of such demographic oscillation can inform conservation plans that support threatened species. Human activities have reduced and fragmented the already restricted habitat of the Phillips's kangaroo rat (Dipodomys phillipsii), threatening its existence. The objective of this study was to describe and analyze D. phillipsii’s annual population cycle and structure in the context of its increasing vulnerability to extinction. The capture-recapture technique was performed monthly from 2012 to 2016. Total individual counts, age, reproductive condition, weight, and sex of D. phillipsii were determined and recorded. Daily temperature and precipitation data of the study area were analyzed with population parameters and frequency data. D. phillipsii populations responded to changes in temperature and precipitation. The highest population densities were recorded in the spring and summer and were correlated with the highest values of the environmental variables studied. Sex ratio was nearly equal during samplings, with non-pregnant females and males with abdominal testes as the most frequently presented secondary sexual characteristics. Most captured individuals were adults. Individual body weights were highly variable, which can be attributed to reproduction and fluctuations in resource availability. D. phillipsii populations severely decreased in the last year of the study, with low juvenile and pregnant or lactating female frequency counts. Anthropogenic pressures on D. phillipsii habitat persist, indicating that the proliferation of this species is at risk. Information from this study could be used to address the pressing need for the management and conservation of D. phillipsii.